1992
DOI: 10.1530/jrf.0.0940395
|View full text |Cite
|
Sign up to set email alerts
|

Role of progesterone and oestradiol in the regulation of uterine oxytocin receptors in ewes

Abstract: Summary. The interaction between oestrogen and progesterone in the regulation of the uterine oxytocin receptor in sheep was evaluated by measuring the binding of oxytocin to membrane preparations of caruncular and intercaruncular endometrium and myometrium. Ovariectomized ewes were assigned in groups of five to each cell of a 4 \m=x\2 factorial design. The four treatments were (a) vehicle (maize oil) for 12 days, (b) progesterone (10 mg day\m=-\1) for 9 days, (c) progesterone for 9 days followed by maize oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
3

Year Published

1994
1994
2006
2006

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 16 publications
3
17
0
3
Order By: Relevance
“…However, it remains unclear whether the inhalation of cigarette smoke directly enhances the expression of OTR mRNA in the myometrium. Since OTR levels are known to be upregulated through progesterone regression, which occurs during luteolysis in the ewe (Hixon & Flint 1987, Zhang et al 1992, the increased expression of OTR mRNA in the pregnant rat myometrium, in the smoking group, may be caused indirectly through progesterone regression via luteolysis. Thus, inhalation of cigarette smoke may damage the function of the corpus luteum in the pregnant rat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it remains unclear whether the inhalation of cigarette smoke directly enhances the expression of OTR mRNA in the myometrium. Since OTR levels are known to be upregulated through progesterone regression, which occurs during luteolysis in the ewe (Hixon & Flint 1987, Zhang et al 1992, the increased expression of OTR mRNA in the pregnant rat myometrium, in the smoking group, may be caused indirectly through progesterone regression via luteolysis. Thus, inhalation of cigarette smoke may damage the function of the corpus luteum in the pregnant rat.…”
Section: Discussionmentioning
confidence: 99%
“…This uncertainty is based upon the findings that progesterone decreases the levels of uterine OTR mRNA and protein in pregnant rats (Soloff et al 1983), and estrogen increases the levels of OTR in the rat uterus and in human-cultured myometrial cells (Soloff 1975, Adachi & Oku 1995. Additionally, it has been reported that OTR levels are upregulated through progesterone regression, which occurs during luteolysis in the ewe (Hixon & Flint 1987, Zhang et al 1992. Therefore, the increased expression of OTR mRNA in the pregnant rat myometrium in the smoking group may be caused indirectly through progesterone regression via luteolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns experimentos indicaram inclusive um possível efeito inibitório do E2 nos OTR na ausência de pré-exposição à P4 (VALLET et al, 1990;ZHANG et al, 1992), enquanto o E2 após exposição à P4, causa grande estímulo à expressão de OTR e à secreção de PGF2α estimulada pela OT em bovinos e ovinos (LAU et al, 1993;KAMINSKI et al, 1997;WALKER et al, 1997). É possível, portanto, que a pré-exposição à P4 seja necessária para que o E2 exerça seus efeitos clássicos mais relevantes sobre o endométrio.…”
Section: Aspectos Moleculares Relacionados à Luteóliseunclassified
“…Estudos em ovelhas demonstraram que apenas a queda na concentração circulante de P4 foi suficiente para iniciar a expressão de OTR, mas a administração de E2 no momento da retirada da P4 maximizou o estímulo à expressão gênica de OTR (LEAVITT et al, 1985;VALLET et al, 1990;ZHANG et al, 1992). Além disso, diversos estudos in vivo demonstraram que o E2 estimula a expressão endometrial de OTR (HIXON & FLINT, 1987;BEARD & LAMMING, 1994;SPENCER et al, 1995) e um estudo in vitro confirmou o efeito do E2 em acelerar a expressão gênica de OTR sem, no entanto, alterar a concentração final de mRNA de OTR (LEUNG & WATHES, 1999).…”
Section: Aspectos Moleculares Relacionados à Luteóliseunclassified
See 1 more Smart Citation